2006
DOI: 10.1007/s00213-006-0471-7
|View full text |Cite
|
Sign up to set email alerts
|

Driving impairment in depressed patients receiving long-term antidepressant treatment

Abstract: The depressed patients receiving long-term treatment with SSRI- and SNRI-type antidepressants show impaired driving performance. This impairment in driving performance can probably be attributed to residual depressive symptoms instead of the antidepressant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 24 publications
(20 reference statements)
4
82
2
1
Order By: Relevance
“…It does seem that there is an advantage under SSRI treatment, when compared to patients treated with tricyclics in a clinical routine setting. However, antidepressive treatment may not normalize driving ability, at least in a subgroup of depressed patients (Brunnauer et al 2006(Brunnauer et al , 2008bWingen et al 2006).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It does seem that there is an advantage under SSRI treatment, when compared to patients treated with tricyclics in a clinical routine setting. However, antidepressive treatment may not normalize driving ability, at least in a subgroup of depressed patients (Brunnauer et al 2006(Brunnauer et al , 2008bWingen et al 2006).…”
Section: Resultsmentioning
confidence: 98%
“…Two patient studies were undertaken to examine the effects of long-term treatment with tricyclics, SSRIs, venlafaxine and mirtazapine on either psychomotor functions related to driving skills (Brunnauer et al 2006) or on actual driving performance in an on-road driving test (Wingen et al 2006). In both studies, it could be demonstrated that most depressive patients under steady-state pharmacologic treatment were below healthy control performance.…”
Section: All Antidepressantsmentioning
confidence: 99%
“…Although it has not been thoroughly outlined in the current review, it is essential to driver safety that the driving-related effects of all types of antidepressant medication are well understood. Some past research has confounded the effects of depression with its treatment medication (e.g., Wingen et al 2006), and other studies have looked at the impact of antidepressants on healthy drivers (Brunnauer and Laux 2013). The advancement of driver simulation technology presents an excellent opportunity to address this research question and to resolve methodological limitations of previous investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that depression may affect driving skills and behaviours (e.g., Selzer and Vinokur 1975;Wingen et al 2006); however, there is surprisingly little research examining the impact of depression on driver performance and collision risk (Dobbs 2005;Hollister 1992). Most previous reviews of this literature are restricted to the 'grey literature', have been based on a relatively small number of studies, and have been inconclusive (Charlton et al 2004;Dobbs 2005;Marshall 2008;Vaa 2003).…”
mentioning
confidence: 99%
“…De resultaten lieten zien dat de rijvaardigheid niet verbeterde na zes weken behandeling met fluoxetine of moclobemide, ondanks een verbetering van depressieve klachten (Ramaekers et al, 1997). Het langetermijneffect van antidepressivagebruik door depressieve patie¨nten op cognitie en rijvaardigheid, direct op de weg gemeten, werd onderzocht in een recent onderzoek (Wingen et al, 2006). De verwachting was dat de rijvaardigheid en het cognitief functioneren van depressieve patie¨nten behandeld met niet-sedatieve antidepressiva vergelijkbaar zou zijn met die van gezonde vrijwilligers, aangezien de antidepressiva die tegenwoordig vaak worden voorgeschreven minder bijwerkingen hebben en de depressie verlichten.…”
Section: Depressie En Rijvaardigheidunclassified